Pengaruh Servant Leadership terhadap Work Role Performance dimediasi oleh Knowledge Sharing pada Karyawan PT Bank Nagari Cabang Utama Sumatera Barat - Pranata, Revaldo; Andriani, Chichi (Lembaga Yasin AlSys, 2025)
Work role performance is a critical aspect in addressing the complexities of modern organizational dynamics. This study aims to analyze the influence of servant leadership on work role performance and to examine the mediating role of knowledge sharing in this relationship among employees at PT. Bank Nagari, Main Branch, West Sumatra. Initial observations revealed issues such as low initiative, adaptability, and self-confidence among employees, indicating weak work role performance. The study employed a quantitative approach with a causal associative design. Data were collected via questionnaires distributed to 133 permanent employees, selected through cluster proportional random sampling from a total population of 198. Data analysis was conducted using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) method via SmartPLS software. The results show that (1) servant leadership has a positive and significant effect on work role performance; (2) servant leadership positively and significantly influences knowledge sharing; (3) knowledge sharing has a positive and significant impact on work role performance; and (4) knowledge sharing significantly mediates the relationship between servant leadership and work role performance. The study concludes that servant leadership enhances employee performance both directly and indirectly by fostering a culture of knowledge sharing. The practical implication is that organizations should promote participatory leadership styles and establish systematic knowledge-sharing systems to develop proactive, adaptive, and competent employees.